Ways to Develop Modern Bank Services - Ruzimamatovich, Norov Akmal; Abutalipovna, Abdusattarova Shaxida; o‘g‘li, Adashaliyev Baxtiyorjon Valisher; o’g’li, Akbarov Husniddinjon Mo’ysin; qizi, Xodjayeva Jeyrona Ravshonbek (European Journal of Life Safety and Stability (2660-9630), 2021)
This article describes in detail the formation of modern types of banking services, its role and importance in the organization of banking services. It has been revealed that digital banking services are one of the foundations for banks to enter the new system and its convenience. It also shows the capabilities of remote banking services provided through the application "Mobile banking" and discusses the risks in this process. In addition, the reforms being implemented in the country to further improve the quality of customer service of banks and the convenience created for the population to use banking services were analyzed. Also, scientific and practical recommendations on the areas of further development and improvement of remote banking services provided by banks through the application of "Mobile banking" and improving its quality were proposed.